Shalom, bitches: Epistemic stance and identity work in an anonymous online forum. (March 2017) - Jacknick, Christine M.; Avni, Sharon
Abstract: How individuals discursively identify themselves through digital media and augment their claims of knowledge and legitimacy is at the core of this study. This article draws on the tools of Conversation Analysis to show how participants discussing the approval of a Hebrew language charter school in an online community forum claim access to particular kinds of knowledge and expertise through linguistic and interactional means. We ask: given the particular constraints and affordances of an asynchronous, anonymous online forum, how do participants position themselves and others with regard to identity? Despite the asynchronous nature of the forum, we show how such identity work is accomplished interactionally through the use of online affordances, as participants position themselves and others to bolster their epistemic stance, or to weaken the epistemic claims of others.